2017
DOI: 10.1126/science.aan3351
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell methylomes identify neuronal subtypes and regulatory elements in mammalian cortex

Abstract: The mammalian brain contains diverse neuronal types, yet we lack single-cell epigenomic assays able to identify and characterize them. DNA methylation is a stable epigenetic mark that distinguishes cell types and marks regulatory elements. We generated >6,000 methylomes from single neuronal nuclei and used them to identify 16 mouse and 21 human neuronal subpopulations in the frontal cortex. CG and non-CG methylation exhibited cell type-specific distributions and we identified regulatory elements with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
650
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(683 citation statements)
references
References 41 publications
31
650
0
2
Order By: Relevance
“…Immune-enrichment methods using antibodies against native proteins such as NeuN (Lister et al, 2013) or transgenic methods as shown by the Ecker and Allen Institute groups (Gray et al, 2017; Mo et al, 2015) followed by FACS or affinity purification have allowed construction of high resolution epigenomic maps of purified populations from human and mouse brains including excitatory, inhibitory as well as non-neuronal cells. More recently, the Ecker group developed a new single-nucleus methylome sequencing method called snmC-seq, which allowed a direct comparison of cell-type composition in mouse and human cortices using ~6000 cells and identified 16 mouse and 21 human neuronal subpopulations in the frontal cortex along with regulatory elements with differential methylation across neuron types (Luo et al, 2017). …”
Section: Single-cell Epigenomicsmentioning
confidence: 99%
“…Immune-enrichment methods using antibodies against native proteins such as NeuN (Lister et al, 2013) or transgenic methods as shown by the Ecker and Allen Institute groups (Gray et al, 2017; Mo et al, 2015) followed by FACS or affinity purification have allowed construction of high resolution epigenomic maps of purified populations from human and mouse brains including excitatory, inhibitory as well as non-neuronal cells. More recently, the Ecker group developed a new single-nucleus methylome sequencing method called snmC-seq, which allowed a direct comparison of cell-type composition in mouse and human cortices using ~6000 cells and identified 16 mouse and 21 human neuronal subpopulations in the frontal cortex along with regulatory elements with differential methylation across neuron types (Luo et al, 2017). …”
Section: Single-cell Epigenomicsmentioning
confidence: 99%
“…This method takes advantages of random priming and extension, after which the samples are end‐tailed and ligated to adaptor in one‐pot. snmC‐seq has the capability to classify large‐scale cell types through multiplex reactions with higher mapping ratesequencing and single‐cell post bisulfite adaptor tagging sequencing.…”
Section: Single‐cell Profiling Methods For Dna Modificationsmentioning
confidence: 99%
“…Several groups including those lead by Reik (Angermueller et al 2016;Clark et al 2016;Clark et al 2017), Vijg (Gravina et al 2015Gravina et al 2016;Yu et al 2017), Adey (Mulqueen et al 2017), and Eckardt (Luo et al 2017) have also demonstrated that methylation patterns can be generated from single cells. However, the principle caveat to these methods is that only a small amount of the genome is analyzed (often around 5%) and the same genomic regions are not analyzed in each cell, making cell-to-cell comparisons of specific loci difficult.…”
Section: Single Cell/cell-type Analysesmentioning
confidence: 99%